Antagonistic role of natural compounds in mTOR-mediated metabolic reprogramming. Issue 2 (28th January 2015) - Cerella, Claudia; Gaigneaux, Anthoula; Dicato, Mario; Diederich, Marc
Abstract: Cells reprogram their metabolism very early during carcinogenesis; this event is critical for the establishment of other cancer hallmarks. Many oncogenes and tumor suppressor genes control metabolism by interplaying with the existing nutrient-sensing intracellular pathways. Mammalian target of rapamycin, mTOR, is emerging as a collector and sorter of a metabolic network controlling upstream and downstream modulation of these same genes. Natural compounds represent a source of anti-cancer molecules with chemopreventive and therapeutic properties. This review describes selected pathways and genes orchestrating the metabolic reprogramming and discusses the potential of natural compounds to target oncogenic metabolic aberrations.